Novel pfkelch13 Gene Polymorphism Associates With Artemisinin Resistance in Eastern India. (9th December 2018) - Das, Sabyasachi; Manna, Subhankar; Saha, Bhaskar; Hati, Amiya Kumar; Roy, Somenath
Abstract: Background: Artesunate-sulfadoxine-pyrimethamine (ASSP) is the frontline artemisinin combination therapy (ACT) in India. Random, irrational, subtherapeutic artemisinin doses and self-medication with ACT along with predominance of sulfadoxine-pyrimethamine resistance parasite invoked a strong possibility of emerging artemisinin-resistant malaria parasites. Methods: This study involved 226 patients with uncomplicated Plasmodium falciparum infection who had successfully completed the 42 days follow-up after ASSP combination therapy from April 2014 to January 2016. We assessed the ASSP treatment efficacy by evaluating parasite clearance half-life, pfkelch13, and other ( pfdhfr, pfdhps, pfmdr1, pfcrt ) gene mutations and survival of parasites as detected by an ex vivo ring-stage survival assay (RSA). Findings: Slow-clearing infections with longer parasite clearance half-lives (>5 hours) were observed in 12% isolates. Cure rate after ASSP treatment was declining to about 84.1%. ASSP failure was recorded in 15.9% (early treatment failure, 7.9%; late treatment failure, 7.9%) of isolates. In sum, 24 patients (10.6%) had parasite clearance half-lives greater than 5 hours with pfkelch13 polymorphism after 441 codon; in 15 of those patients (6.6%), parasites had not cleared by 72 hours after initiation of therapy. Median ex vivo ring-stage survival rate of these isolates was very high (12.2%; 95% confidence interval [CI], 10.9–13.8) from that of cured patients (0.9%; 95% CI, 0.09–1.07). Of these 15 patients, 13 patients had pfkelch13 G625R polymorphism, whereas 2 patients contained R539T polymorphism. As per the World Health Organization guideline, these 15 isolates were true artemisinin-resistant isolates. Interpretation: Identification of artemisinin-resistant isolates in India together with new mutations and increasing combination therapy failures blow alarms for urgent malaria control. Abstract : We report novel pfkelch 13 polymorphism associated artemisinin resistance leading to artemisinin combination therapy treatment failure for the first time to our knowledge in Eastern India. The findings call for urgent revision of the protocol for malaria treatment.